2004
DOI: 10.1152/jn.01151.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Anesthetic Tricaine (MS-222) on Nerve Activity in the Anterior Lateral Line of the Oyster Toadfish,Opsanus tau

Abstract: Inductive neural telemetry was used to record from microwire electrodes chronically implanted into the anterior lateral line nerve of the toadfish, Opsanus tau. Spontaneous neural activity and the response of lateral line fibers to water current were continually monitored from 17 primary afferent fibers before, during, and after the administration of the anesthetic tricaine (MS-222). Significant decrease in spontaneous and evoked activity and increase in interspike interval was noted when anesthetic concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 17 publications
0
52
1
Order By: Relevance
“…We did not find a similar reduction of AEP amplitude following brief sedation using 0.01% MS222. The difference may be due to the compound nature of the AEP, as opposed to the single unit activity recorded by Palmer and Mensinger (2004). More likely, it is due to the brevity of MS222 exposure in the present report.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…We did not find a similar reduction of AEP amplitude following brief sedation using 0.01% MS222. The difference may be due to the compound nature of the AEP, as opposed to the single unit activity recorded by Palmer and Mensinger (2004). More likely, it is due to the brevity of MS222 exposure in the present report.…”
Section: Discussionmentioning
confidence: 60%
“…Palmer and Mensinger (2004) showed that anesthesia with MS-222 at dosages greater than 0.01% decreases spontaneous and stimulus-evoked activity in anterior lateral line nerve afferents. We did not find a similar reduction of AEP amplitude following brief sedation using 0.01% MS222.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 0.009 % MS-222 concentration used in this study can sufficiently anesthetize one-week old zebrafish. Palmer and Mensinger (2004) reported that MS-222 concentrations lower than 0.01 % did not significantly reduce either spontaneous or evoked responses of sensory fibers innervating hair cells in the anterior lateral line of the toadfish. Although they did observe suppression of lateral line afferent response at higher MS-222 concentrations, it is not known whether the suppressive effects result from MS-222 action on hair cells, sensory afferents, or both.…”
Section: Factors Affecting the Microphonic Potential Recordingmentioning
confidence: 95%